Erikson’s Development Psychosocial Theory In The 21st Century: A Pedagogical Perspective In Physical Education - Herdiansyah Herdiansyah; Agil Meilana; Carsiwan Carsiwan; Dewi Susilawati (UNIVERSITAS NEGERI MAKASSAR, 2024)
This literature review aims to understand Erik Erikson's psychosocial development theory and its relevance in physical education in the 21st century. This theory emphasizes the importance of resolving psychosocial crises at every stage of human development. The study explores Erikson's eight stages of psychosocial development, ranging from the trust vs. mistrust stage to the integrity vs. despair stage. In physical education, Erikson's theory provides insights into developing curricula and teaching methods that align with students' psychosocial developmental needs. The review analyzes how physical education can resolve psychosocial crises through appropriately designed physical activities, games, and sports. Furthermore, the study explores the challenges and opportunities in implementing Erikson's theory in 21st-century physical education. Evolving social changes, technology, and cultural trends influence students' psychosocial development dynamics. Therefore, adaptive and innovative pedagogical approaches are necessary to ensure physical education's relevance and effectiveness in meeting students' psychosocial developmental needs in the modern era. The review highlights the importance of understanding students' psychosocial developmental stages and tailoring physical education experiences accordingly. It examines the role of physical education in fostering trust, autonomy, initiative, industry, identity, intimacy, generativity, and integrity – the key developmental tasks outlined by Erikson. Additionally, the review discusses strategies for creating inclusive and supportive learning environments that promote positive psychosocial development through physical activity. This literature review provides valuable insights for educators, researchers, and stakeholders in physical education by offering a comprehensive theoretical perspective and practical recommendations for integrating the principles of psychosocial development into curricula and teaching practices in the 21st century. It emphasizes the need for a holistic approach to physical education that not only enhances physical fitness but also nurtures students' psychological and social well-being, preparing them for lifelong personal growth and societal contribution.